Successful management of pregnancy in a non-communicating rudimentary horn of a unicornuate uterus - R., Sasirekha; Rani, Reddi P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Pregnancy in a rudimentary horn pregnancy is a rare clinical condition. The usual consequence is rupture culminating in hypovolemic shock. We had a different scenario of unruptured rudimentary horn pregnancy which was detected following failed attempt of MTP. She underwent laparotomy and excision of rudimentary horn. Post-operative period was uneventful. We present this case not only because of rarity but also high index of suspicion is required to diagnose at an early stage before a devastating course.